Early Abnormal Placentation and Evidence of Vascular Endothelial Growth Factor System Dysregulation at the Feto-Maternal Interface After Periconceptional Alcohol Consumption - Gualdoni, Gisela Soledad; Jacobo, Patricia Verónica; Barril, Camila; Ventureira, Martín Ricardo; Cebral, Elisa (Frontiers in Physiology, 2022)
Adequate placentation, placental tissue remodeling and vascularization is essential for the success of gestation and optimal fetal growth. Recently, it was suggested that abnormal placenta induced by maternal alcohol consumption may participate in fetal growth restriction and relevant clinical manifestations of the Fetal Alcohol Spectrum Disorders (FASD). Particularly, periconceptional alcohol consumption up to early gestation can alter placentation and angiogenesis that persists in pregnancy beyond the exposure period. Experimental evidence suggests that abnormal placenta following maternal alcohol intake is associated with insufficient vascularization and defective trophoblast development, growth and function in early gestation. Accumulated data indicate that impaired vascular endothelial growth factor (VEGF) system, including their downstream effectors, the nitric oxide (NO) and metalloproteinases (MMPs), is a pivotal spatio-temporal altered mechanism underlying the early placental vascular alterations induced by maternal alcohol consumption. In this review we propose that the periconceptional alcohol intake up to early organogenesis (first trimester) alters the VEGF-NO-MMPs system in trophoblastic-decidual tissues, generating imbalances in the trophoblastic proliferation/apoptosis, insufficient trophoblastic development, differentiation and migration, deficient labyrinthine vascularization, and uncompleted remodelation and transformation of decidual spiral arterioles. Consequently, abnormal placenta with insufficiency blood perfusion, vasoconstriction and reduced labyrinthine blood exchange can be generated. Herein, we review emerging knowledge of abnormal placenta linked to pregnancy complications and FASD produced by gestational alcohol ingestion and provide evidence of the early abnormal placental angiogenesis-vascularization and growth associated to decidual-trophoblastic dysregulation of VEGF system after periconceptional alcohol consumption up to mid-gestation, in a mouse model.